The Rise of K-Popper’s Political Awareness in Twitter and What It Means for All of Us - Dani Fadillah; Arif Ardy Wibowo; Nunik Hariyati; Bai Long; Luo Zhenglin (Jurnal Ilmu Komunikasi, 2021)
The Omnibus Law, which was passed on October 5, 2020, has discontented students and workers who protested on the streets. The ratification of the Omnibus Law has an effect on public opinion-raising activities, both those who support and who reject the ratification of the Omnibus Law, are crowded on Twitter social media. The active account of K-Poppers who took part became a line against the opinion of the Omnibus Law, so a question arises whether this is a phenomenon of the rise of political awareness of K-Poppers in Indonesia? This study analyzes the role of K-Poppers in socio-political movements in several countries globally, especially in Indonesia. The type of research used is a case study of the K-Poppers movement in the case of the ratification of the Omnibus Law as the subject in writing this paper. Collecting data using Social Network Analysis (SNA) and observing the activities of K-Poppers in Indonesia when parliament passed the controversial Omnibus Law. The results of this study indicate that Indonesian K-Poppers maximize their function as part of Indonesian citizens to express their political stance. They also showed their political involvement when creating hashtags, organizing other K-Pop crowds, and at the same time providing support to activists who rejected the Omnibus Law.